TINJAUAN MAQASID SYARI’AH TERHADAP JASTICE COLLABORATOR - Nasruddin Khalil Harahap; Hendra Gunawan (STAI Tuanku Tambusai, 2023)
This article describes the jastice collaborator, which is seen from the perspective of maqasidsyari'ah, this paper wishes to see this term justice collaborator from the point of view of itsbenefits for victims of crime and society in general. To find out this aspect of benefit, theauthor uses the maqasid sharia principles as a measuring tool to detect whether there is benefitcontained in the term justice collaborator. The methodology that the author uses in this paperis a qualitative descriptive model, starting from describing the phenomenal collaborators thatoccur in society, then looking at them from the elements of the benefits and benefits of theterm jastice collaborator, both benefits and intentions that have a direct impact on actors andsociety in general , finally the author analyzes it from the perspective of maqasid sharia,namely through several maqasid sharia rules related to benefit. The findings in thisinvestigation, that the term justice collaborator when viewed from the perspective of maqasidshari'ah has relevance to the maqasid sharia principles of upholding justice, because thepurpose of this justice collaborator is to uncover a case to its roots, this is in line with maqasidsharia realizing beneficence and justice.